2009
DOI: 10.1002/ddrr.74
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric conditions associated with prenatal alcohol exposure

Abstract: Since the identification of fetal alcohol syndrome (FAS) over 35 years ago, mounting evidence about the impact of maternal alcohol consumption during pregnancy has prompted increased attention to the link between prenatal alcohol exposure (PAE) and a constellation of developmental disabilities that are characterized by physical, cognitive, and behavioral impairments. These disabilities include a continuum of developmental disorders known as fetal alcohol spectrum disorders (FASDs). Longitudinal studies suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
129
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(139 citation statements)
references
References 78 publications
5
129
0
5
Order By: Relevance
“…3 Unfortunately, many children and adolescents with FASD go unrecognized and untreated [6][7][8] ; this is due to multiple factors, including unknown maternal history of alcohol use during pregnancy, 9,10 lack of consistent facial dysmorphology and growth impairment across all diagnoses within the fetal alcohol spectrum, 3,4,10,11 and the high rate of cooccurring mental health disorders. 12 Within our clinic's population at the Children's Research Triangle (CRT), it was noted that large numbers of children with FASD had been incorrectly diagnosed before referral. The purpose of this article is to assess the rate of misdiagnosis and missed diagnoses of FASD among a population of children and adolescents referred to a children's mental health center for assessment and treatment.…”
mentioning
confidence: 99%
“…3 Unfortunately, many children and adolescents with FASD go unrecognized and untreated [6][7][8] ; this is due to multiple factors, including unknown maternal history of alcohol use during pregnancy, 9,10 lack of consistent facial dysmorphology and growth impairment across all diagnoses within the fetal alcohol spectrum, 3,4,10,11 and the high rate of cooccurring mental health disorders. 12 Within our clinic's population at the Children's Research Triangle (CRT), it was noted that large numbers of children with FASD had been incorrectly diagnosed before referral. The purpose of this article is to assess the rate of misdiagnosis and missed diagnoses of FASD among a population of children and adolescents referred to a children's mental health center for assessment and treatment.…”
mentioning
confidence: 99%
“…We found that early irritability and poor mother-child interactions in the more heavily exposed infants at 1 year of age predicted higher levels of depression at 6 years of age, particularly for girls [8]. These findings emerged even though the mothers had not been identified as high-risk drinkers and the children were functioning within the high average range of intelligence.…”
Section: Infancy and Early Childhoodmentioning
confidence: 68%
“…Longitudinal studies suggest that individuals with PAE are at an increased risk for adverse long-term outcomes, including mental health problems and poor social adjustment [8]. This review summarizes the current literature on the underlying mechanisms of PAE vulnerability, including epigenetic, genetic, and environmental risk factors that predispose individuals with PAE to psychiatric illness.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, this appears to be changing, as research in the field of interventions is growing. O'Connor and Paley [77] recommended an exploration of how existing treatments may be adapted to suit the FASD population, ways to evaluate efficacy of multi-level approaches that attempt to respond to the broad range of issues present for those with FASD, and how to effectively translate research into practice.…”
Section: Resultsmentioning
confidence: 99%